Joseph Conrad's Nautical Terms : A Handbook - Larabee, Marc D. (Conrad Studies, 2025)
Unlock the secrets of Conrad's salt-laced realm! Discover the meanings of "wearing ship," "kedge anchors," or the perils of "scudding under bare poles." Joseph Conrad's Nautical Terms demystifies 2,000 maritime words and phrases, revealing how Conrad used them to create his legendary narratives. Rich historical sources, clear glossary definitions, informative illustrations, and 600 detailed examples from his writing combine to decode and bring to life his nautical world. Explore his thrilling storm passages, evocative calm scenes, rigorous examinations, and remarkable journey from sailor to shipmaster-and even learn the ropes of the Beaufort wind scale. Whether you're a Conrad enthusiast, student, or sea lover, this book transforms your reading experience, making every voyage with him a deeper, more immersive adventure.